(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the prevalence of Helicobacter pylori infection detected by esophagogastroduodenoscopy and to assess associated factors among patients undergoing endoscopy at a district hospital. Methods: A cross-sectional descriptive study was conducted on 391 patients who underwent esophagogastroduodenoscopy with urease testing for H. pylori diagnosis at My Duc General Hospital from March 2025 to August 2025. Associations were assessed using univariate logistic regression and presented as crude odds ratios (OR) with 95% confidence intervals. Results: The mean age was 53.25 ± 15.41 years; 67.0% were female. The prevalence of H. pylori infection was 38.9%. Female patients had a higher prevalence than males (OR=1.75; 95%CI: 1.12–2.74). Patients aged ≤60 years had a higher prevalence than those >60 years (OR=1.62; 95%CI: 1.05–2.50). Smoking (OR=1.91; 95%CI: 1.16–3.15) and alcohol use (OR=1.58; 95%CI: 1.02–2.45) were associated with higher prevalence. Conclusion: The prevalence of H. pylori infection among endoscopy patients was relatively high. Several factors were associated in univariate analysis; further studies using multivariate models are needed.